2022
DOI: 10.1093/jxb/erac448
|View full text |Cite
|
Sign up to set email alerts
|

Cellobiose elicits immunity in lettuce conferring resistance toBotrytis cinerea

Abstract: Cellobiose is the primary product of cellulose hydrolysis and is expected to be served as pathogen/damage-associated molecular patterns (PAMPs/DAMPs) in evoking plant innate immunity. In the study, cellobiose was demonstrated to be a positive regulator in immune response, but devote to halt autoimmunity when lettuce was exposed to cellobiose higher than 60 mg·L –1. When infected by Botrytis cinerea, cellobiose endowed plants with enhanced pre-invasion resistance by activating high levels of β-1,3-glucanase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Furthermore, sugar metabolites trigger immune responses. CB elicits immunity in lettuce [ 46 ] and Arabidopsis [ 51 ], and stimulates SUC1 and STP4 expression [ 67 ]. Fructans prime ROS dynamics and Botrytis cinerea resistance [ 76 ], while trehalose modulates defense responses in Arabidopsis [ 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, sugar metabolites trigger immune responses. CB elicits immunity in lettuce [ 46 ] and Arabidopsis [ 51 ], and stimulates SUC1 and STP4 expression [ 67 ]. Fructans prime ROS dynamics and Botrytis cinerea resistance [ 76 ], while trehalose modulates defense responses in Arabidopsis [ 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kohorn et al [ 45 ] have shown that cell wall sensing via pectin breakdown regulates the vacuolar invertase involved in the solute sugar metabolism. The cellulose breakdown product cellobiose (CB) stimulates the primary sugar metabolism and evokes innate immune responses [ 46 ]. The stimulation of immune responses by cellooligomers may result in a shift of the growth/defense balance towards defense, which not only inhibits growth and activates defense gene expression but also affects the amino acid profile [ 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cellobiose is the primary product of cellulose hydrolysis and is expected to function as a type of pathogen/damage-associated molecular pattern in evoking plant innate immunity [ 26 ]. We identified this compound only in roots and stems.…”
Section: Discussionmentioning
confidence: 99%
“…This product of cellulose hydrolysis may actually function as a type of pathogen/damage-associated molecular pattern to induce plant innate immunity. He and colleagues [ 193 ] determined that below 60 mg L −1 , cellobiose administered on lettuce can have positive effects on plant response to B. cinerea by activating high activities of β-1,3-glucanase and antioxidant enzymes at the early stage of pathogen infection. Interestingly, EDS1, PTI6, and WRKY70, which are cellobiose-activated core regulatory factors such as SA signaling, played a crucial role in modulating plant responses.…”
Section: Further Aspects Related To Plant Immunity and An Overview Of...mentioning
confidence: 99%